Jugendbewegung, Antisemitismus und rechtsradikale Politik Vom "Freideutschen Jugendtag" bis zur Gegenwart - Botsch, Gideon; Haverkamp, Josef (Europäisch-jüdische Studien - Beiträge, 2014)
The year 2013 marks the centennial of the first "Free-German Youth Day" that took place on the Meissner massif. Anti-Semitic outbursts erupted at the margins of this historical gathering. In its wake, a right-wing populist faction of the youth movement arose for the first time. This collected volume examines the interface between the youth movement, nationalism, and anti-Semitism.